Environmental safety of soils in conditions of intensive agricultural land use - A. N. Nekos; O. I. Khripko; O. O. Bolotova (Людина і довкілля: Проблеми неоекології)
For the sustainable functioning of agroecosystems and sustainable food supply of the population, the task of ensuring the ecological safety of soils in the conditions of using intensive technologies for growing agricultural crops is relevant.